Evaluating the immunopathological effects of nigella sativa oil and its major component, thymoquinone in a streptozotocin-induces type1 diabetes rat model / Afaf Jamal Ali Hmza - Ali Hmza, Afaf Jamal (2013)
Type 1 diabetes mellitus (T1DM) is considered as an autoimmune disease. It is characterised by the presence of antibody (humoral) and T-cell (cellular) responses to islet proteins (antigens). Nigella sativa oil and its major component thymoquinone (TQ) have been documented to have hypoglycemic properties in both type 1 and type 2 diabetes, but to the best of our knowledge the effect of this plant on the immunopathology of IDDM has never been examined.The objectives of this study were to determine the potential immunomodulatory effect of administration of Nigella sativa oil and it major compound thymoquinone (TQ) in the disease process of IDDM by assessing the levels of anti- islet cell antibodies, pan T- lymphocytes marker (CD90), pan B-lymphocytes markers (CD19), and pan innate cells marker (CD 1 lb).Method: Type 1 diabetic state was induced to overnight fasted animals by intraperitoneal injection with a single dose of STZ (65 mg/kg body weight). Six equal sized groups of male Sprague- Dawley rats received or not different doses of N. sativa oil and TQ. Blood glucose was tested every morning through 30 days of the experimental period. After completion of the 4 weeks experimental protocols, blood samples were collected from overnight fasted rats by the cardiac puncture under anesthesia. Serum was assayed for autoimmune anti- Islet cell antibodies (ICA), pan T- lymphocytes marker (CD90), pan B lymphocytes marker (CD 19), and pan innate cells marker (CD1 lb) in addition to serum insulin using enzyme linked immunosorbent assay (ELISA) . The animals were dissected after sacrificed and the pancreas was taken for histology. This organ was placed in 10% formalin for fixation. Results: T1DM causes increased the levels of serum glucose, levels of T, B lymphocytes markers, innate cells marker, and ICA and decreased serum insulin level, meanwhile treatment of diabetic rats with N. sativa oil and TQ significantly decrease the levels of all immunological (p< 0.05) beside it significantly resulted in elevation of serum insulin level (p< 0.05). The study also emphasized that, N. sativa oil and TQ are effective against STZ diabetes as its administration ameliorated most of the pathological changes.Conclusions: These experimental results indicate the immunomodulatory effect of N.sativa against autoimmune reactions occurs in T1DM. This data provide new strategies for using this plant to be recommended in the clinical management, control, and prevention of T1DM. Moreover, N. sativa oil and TQ may be suggested to be used in the management of other autoimmune diseases.